Principal Component Analysis: IPSR Innovation Profile - Hafeez, Mohsin; Awan, W. (CGIAR System Organization, 2024)
Principal Component Analysis (PCA) is an effective approach that helps to identify and pinpoint critical locations for monitoring groundwater resources. The approach utilizes statistical techniques to integrate various environmental parameters such as land use, hydrology, climate, and soil attributes to gauge the susceptibility of regions to groundwater quality and quantity. IWMI piloted this approach together with the Government of Punjab, Pakistan, where it is empowering government stakeholders to make collaborative decisions for targeted groundwater interventions. This includes where to install groundwater monitoring devices.